2017
DOI: 10.1590/s1517-707620170003.0186
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anticorrosion performance of peel garlic extract as corrosion inhibitor for ASTM 1020 carbon steel in acidic solution

Abstract: Metallic corrosion can be delayed using corrosion inhibitors. However, several industrial corrosion inhibitors are toxic and harmful to the environment and to the human health. In this context, in the last decades, research has been developed to investigate the performance of low toxicity corrosion inhibitors as green inhibitors obtained from vegetables, which are environmentally acceptable. The present work studied the corrosion inhibition efficiency of peel garlic extract (Allium sativum. L.) for possible re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 19 publications
2
35
0
5
Order By: Relevance
“…There are several reviews on the use of plant extracts as corrosion inhibitors (Migahed and Sabagh, 2009). The literature has shown that plant material such as Aloe Vera extraxt (Eddy & Odoemelam 2009), Aquilaria Crassna Leavees Extract (Helen et al, 2014), Garli (Barreto et al, 2017), Holy Basil (Tulsi) (Kumpawat et al, 2012) and Ginger (Narenkumar et al, 2017) has potential as corrosive inhibitors. Effects of Aloe vera extract on corrosion and kinetics of corrosion process of zinc in HCl solution also studied (Abiola, 2010).…”
Section: Development Of Corrosion Inhibitorsmentioning
confidence: 99%
“…There are several reviews on the use of plant extracts as corrosion inhibitors (Migahed and Sabagh, 2009). The literature has shown that plant material such as Aloe Vera extraxt (Eddy & Odoemelam 2009), Aquilaria Crassna Leavees Extract (Helen et al, 2014), Garli (Barreto et al, 2017), Holy Basil (Tulsi) (Kumpawat et al, 2012) and Ginger (Narenkumar et al, 2017) has potential as corrosive inhibitors. Effects of Aloe vera extract on corrosion and kinetics of corrosion process of zinc in HCl solution also studied (Abiola, 2010).…”
Section: Development Of Corrosion Inhibitorsmentioning
confidence: 99%
“…Where: 96500 C.mol -1 represents the value of the Faraday's constant and E qmetal is the equivalent-gram of the electrode used. In this research, the work electrode is carbon steel, whose value was 27.93 g, corresponding to pure iron [26].…”
Section: Gravimetric Testsmentioning
confidence: 99%
“…Na literatura é possível verificar exemplos de trabalhos reportados na área de inibidores de corrosão de origem vegetal, Tagetes erecta (Mourya et al, 2014); Salvia officiallis (RODRIGUEZ-TORRES et al, 2015); Hibiscus sabdariffa (NAZEER et al, 2015); Plectranthus amboinicus (ANUPAMA et al, 2017); Allium sativum. L. (BARRETO et al, 2017); Ginkgo (QIANG, et al, 2018) Elaeis guineensis Jacq. (SANTOS et al, 2020).…”
Section: Apresentaçãounclassified